PERANCANGAN MEDIA AUDIO VISUAL PROMOSI WISATA BUKIT AUA SARUMPUN KABUPATEN TANAH DATAR - AFFEBY DEPUTRA, Ir. Drs. Heldi, M.Si., Ph.D., Drs. Ariusmedi, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Abstract—The use of information plays an important technology role in supporting the dissemination information about promotions. The rise of the world of advertising using social media is one strategy that is considered effective and efficient to promote and publish tourism. It is undeniable that audio-visual media in the form of video is now often used to promote tourism objects. The selection of video promotion as this final work aims to design informative and communicative Audio Visual Media in building tourism in Tanah Datar Regency. In addition, the presence of this promotional video can later introduce Bukit Aua Sarumpun as one of the favorite tourist destinations for tourists. This design method is through qualitative descriptive method. This means that the data collected is not in the form of numbers, but rather data derived from interviews, field notes, documentation, and official documents. SWOT analysis (strenght, weakness, opportunities, threats). The design of audio visual media in the form of promotional videos is also supported by several other media such as tickets, x-banners, posters, t-shirts, flayers, and hats that are useful to support the main media as promotional mediaKeywords: Aua Sarumpun Hill, Promotion, SWOT Analysis.Kata kunci: Bukit Aua Sarumpun, Promosi, Analisis SWOT